Matters of mind : the university in Ontario, 1791-1951 - McKillop, A. B. (Ontario historical studies series., 1994)
The only comprehensive history of the formative years of higher education in Ontario, this volume examines the shifting nature of moral, intellectual, and social authority as reflected in the development of Ontario's colleges and universities. With special emphasis on social experience and intellectual life, McKillop gives sustained attention to what was included - and what was not - in the teaching of subjects such as theology, classics, history, English, political science, law, medicine, engineering, business, psychology, and sociology. His insights reveal the imperatives that shaped these disciplines, and others, in distinctively Canadian ways. Founded in the nineteenth century by various Christian denominations, the universities of Ontario initially reflected the acrimony and competition that existed between those denominations. Regardless of religious affiliation however, the university founders saw their purpose as the preservation of a basically conservative social order. The deeply held sense of continuity of a 'cultural memory, ' rooted in the moral authority of Christianity and in British institutions and values, profoundly shaped higher education in the province, especially in the humanities. However, the market-driven tenets of an industrial economy took hold in Canada precisely in the years when the universities were founded. Colleges and universities founded to train clergy and a professional elite, and to provide a liberal education, were challenged and gradually transformed by values that linked them to the needs of commerce and industry. The universities were bound to demonstrate their social utility by creating practical and scientific programs. Each university in the province rose in its own way to the challenges posed by the acceptance and increasing enrolment of women, by political, economic, and social issues outside the universities, and by the close intertwining of the university in Ontario, especially the University of Toronto, with the political culture of the province.